An efficient Markov model for reliability analysis of predictive hybrid m-out-of-n systems. - Syed Mohamed, Syed Abdul Rahman Al-Haddad; Jantan, Adznan; Karimi, Abbas; Zarafshan, Faraneh (2011)
In this paper, predictive hybrid redundancy has been extended to large-scale control systems comprising n modules. In m-out-of-n systems, if m-out-of-n modules are in agreement, the system can report consensus; otherwise the system fails. While in our new extension, if there is no agreement, a history record of previous successful result(s) is used to predict the output. In order to analyze the reliability of this system, we present a Markov model based on which the reliability has been computed and compared with m-out-of-n redundancy. The results of simulation demonstrated that the new redundancy improves overall system reliability in all examined scenarios, especially when the number m is large.